2022
DOI: 10.1021/acs.orglett.2c00384
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructive Insertion of Oximes into Coumarins: Modular Synthesis of Dihydrobenzofuran-Fused Pyridones

Abstract: In the presence of a copper catalyst, a series of oximes undergo deconstructive insertion into coumarins to afford structurally interesting dihydrobenzofuran-fused pyridones in moderate to good yields with good functional group compatibility. The reaction likely involves a radical relay annulation, leading to the ring opening of the lactone moiety of the coumarins, and simultaneous formation of three new bonds. The investigation of photoluminescent properties reveals that several obtained compounds may have po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…To carry out the transformation, various reaction conditions were screened ( Table 1 ). The planned reaction was realized very challenging due to the following: 1. the presence of a highly crowded tri-substituted alkene reaction site; 2. a competitive deconstruction of coumarins under copper (I) catalyzed conditions [ 47 ]. Our initial efforts yielded the conversion of coumarins into salicylaldehyde 2a′ under various conditions ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To carry out the transformation, various reaction conditions were screened ( Table 1 ). The planned reaction was realized very challenging due to the following: 1. the presence of a highly crowded tri-substituted alkene reaction site; 2. a competitive deconstruction of coumarins under copper (I) catalyzed conditions [ 47 ]. Our initial efforts yielded the conversion of coumarins into salicylaldehyde 2a′ under various conditions ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…91 Synthesis via deconstructive insertion reaction involving the generation of new structures via the bond cleavage of easily accessible scaffolds has recently attained growing attention from synthetic practitioners. 92 In this regard, Zheng 93 et al in 2022 reported the Cu-catalyzed synthesis of pyridine-fused dihydrobenzofuran derivatives 167 . In their synthetic protocol, coumarins 163 and oximes 164 were reacted in the presence of CuBr (catalyst) along with Li 2 CO 3 (used as an additive) to afford 2,3-dihydrobenzofurans 167 in low to high yields (16–85%) via the destructive insertion of 164 into 163 .…”
Section: Review Of Literaturementioning
confidence: 99%
“…161-164 • C 1 H NMR (600 MHz, CDCl 3 ): δ = 8.42 (s, 1H), 7.61-7.54 (m, 2H), 7.31 (d, J = 8.5 Hz, 1H), 4.41 (q, J = 7.1 Hz, 2H), 1.40 (t, J = 7.1 Hz, 3H). 13 [55].…”
Section: General Procedures For the Synthesis Of Ethyl 2-oxo-2h-chrom...mentioning
confidence: 99%